Health versus income amid COVID-19: What do people value more? - Palma, Marco A.; Huseynov, Samir; Nayga, Jr., Rodolfo M. (PLOS ONE, 2022)
Public efforts to battle COVID-19 have been portrayed as a trade-off between health and the economy in the U.S. public discourse. We investigate how the U.S. general public prioritizes the health and the income dimensions amid COVID-19 using an incentivized instrument with real monetary consequences. We also employ between-subject information treatments highlighting negative health and income consequences of the pandemic. Specifically, participants have to divide monetary contributions between two charitable organizations representing either the health or the income dimension. An overwhelming majority of participants supports both dimensions, with higher monetary contributions to the health dimension (56%) compared to income (44%), but the difference is not large. Only a small fraction of respondents contributes exclusively to the health (10%) or income (5%) dimensions. Increasing the salience of negative health outcomes of COVID-19 raises differential token allocations in favor of the health-oriented charity. This finding is important since the course of COVID-19 will be shaped by the policies governments implement and how the general public reacts to these policies.